Cultural Adaptation of International Students in Mandarin Language Learning in Zhejiang, China - Siti Alimatus Syukriyah; Adisiti Orizanda; Natkitta Thepprasarn; Souphaphone Meuangviengkham; Muhammad Farhan Masrur (International Journal of Chinese Interdisciplinary Studies, 2026)
This investigation is about cultural adaptation of international students learning Mandarin language in Zhejiang, China, through a mixed-methods approach. Quantitative data from a questionnaire (n=32) were combined with qualitative data from semi-structured interviews, using an explanatory sequential design. Quantitative findings showed that integration was the most preferred adaptation strategy (M=4.09), with assimilation, separation, and marginalization being the next most preferred in descending order. Correlation analysis indicated a strong positive correlation between integration and learning outcomes (r=0.717 p<0.001), meaning that students who not only kept touch with their home culture but also actively engaged with the host culture were more likely to demonstrate high levels of participation in the classroom, confidence in communication, and motivation for learning. Assimilation was also found to be significantly positively correlated, whereas marginalization was negatively related to learning outcomes. Thematic analysis of the qualitative data accentuates the role of intercultural contact, the use of good adaptive techniques, and identity negotiation in students' learning experiences. They also indicated that mixing with various peers and using language actively help cultural adjustment and language development. This study based on acculturation theory and sociocultural perspectives, shows that cultural adaptation plays a major role in Mandarin language learning effectiveness. The results add to the literature by focusing on the importance of multicultural classroom interaction and offering teaching suggestions for enhancing Mandarin language teaching for international students.